Evaluation of Status and Constant Anxiety Levels in Basketball Players According to League Ranking - Yalçın Kaya; Tuncay Sarıipek (Türk Spor ve Egzersiz Dergisi)
The aim of this study, is to evaluate the link between anxiety level and the ranking situation teams at the 2008-2009 Beko Basketball Legue. The documents, which are created by Spielberg and his friends, for evaluating normal and anormal people?s state and anxiety level, in the year 1964 and adapted into Turkish by Öner and Le Compte (1983) is used. 8 teams and 72 sportman of Beko Basketball League which has 16 teams, participated into this study. These inventories are applied to the teams at outher zones, except Selcuk University. The points of state and continuous anxiety level of teams which participated in the research are given in the tables, below. It has not been detected any significant differences between the teams that participated in research in statistical means, when they compared in order to their points of ranking in the league and their continuous anxiety level.